2010
DOI: 10.1111/j.1600-0706.2010.18953.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding dispersal strategies following reproductive failure explain low apparent survival of immigrant Temminck's stints

Abstract: In some animal populations, immigrants have lower survival than philopatric individuals. Costs of dispersal or low phenotypic quality of dispersers may explain the pattern. However, apparent adult survival estimates, which describe real survival combined with site fi delity cannot be separated from permanent emigration. Th us, heterogeneity in breeding dispersal propensities of immigrants and philopatrics can bias fi tness correlates of dispersal. Diff erences in breeding dispersal propensities may be caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…(2010) revealed that both natal and breeding dispersal seem to be rare at regional scale (5–50 km). Pakanen et al. (2010, 2011) also observed that individuals recruited to the population as immigrants were more likely to change breeding sites between seasons, especially if they had experienced poor breeding success.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…(2010) revealed that both natal and breeding dispersal seem to be rare at regional scale (5–50 km). Pakanen et al. (2010, 2011) also observed that individuals recruited to the population as immigrants were more likely to change breeding sites between seasons, especially if they had experienced poor breeding success.…”
Section: Discussionmentioning
confidence: 97%
“…, 2006). The population at the Finnish Bothnian Bay is declining, comprising currently of well under hundred individuals (Pakanen et al. , 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haas , Hoover , Pakanen et al . ) and other factors (e.g. age of the dispersing individual and quality of the nest‐site and the mate; Greenwood & Harvey ).…”
Section: Discussionmentioning
confidence: 99%
“…It has notably been shown to affect mate retention and inter-annual site fidelity (Dubois and Cézilly 2002, Naves et al 2006, Boulinier et al 2008, Pakanen et al 2011, migratory movements to wintering grounds (Bogdanova et al 2011, Hoye et al 2012) and potentially individual behavior and time budgets. It can also affect population structure and dynamics in the longterm through dispersal (Danchin et al 1998, Cam et al 2004).…”
Section: Introductionmentioning
confidence: 99%